CRISPR-Sirius: RNA scaffolds for signal amplification in genome imaging. (November 2018) - Ma, Hanhui; Tu, Li-Chun; Naseri, Ardalan; Chung, Yu-Chieh; Grunwald, David; Zhang, Shaojie; Pederson, Thoru
Abstract Clustered regularly interspaced short palindromic repeats (CRISPR) guide RNA scaffolds have been adapted to carry multiple binding sites for fluorescent proteins to enhance brightness for live cell imaging of genomic loci. However, many of these modifications result in guide RNA instability and thus produce lower genome-labeling efficiency than anticipated. Here we introduce CRISPR-Sirius, based on octet arrays of aptamers conferring both enhanced guide RNA stability and brightness, and provide initial biological applications of this platform. Multiple MS2 loops inserted in the first loop of an sgRNA after the spacer sequence stabilize the sgRNA and allow recruitment of multicolor fluorescent proteins for imaging of low-repeat genomic loci.